Reinforced wear-resistant transparent nano coating as well as preparation method and application thereof
By applying an enhanced wear-resistant transparent nanocoating composed of acidic silica sol, epoxy resin and lithozite on the glass surface of the photovoltaic module, the problem of light transmittance reduction caused by dust accumulation is solved, and the coating is highly wear-resistant, transparent and aging resistance is achieved.
Patent Information
- Application Number
- CN202510120412.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-05-02
AI Technical Summary
The glass surface of photovoltaic modules has reduced light transmittance and reduced efficiency due to dust accumulation, and the wear resistance and aging performance of existing coatings are insufficient, making it difficult to meet the needs of long-term use.
A transparent nanocoating with enhanced wear resistance is used, which consists of acid silica sol, epoxy resin, alkaline catalyst and alcohol solvent. A coating with honeycomb surface morphology is prepared by gelation of acid silica sol and phase separation process of epoxy resin, combined with the physical properties of lithososite.
The wear resistance and transparency of the coating are significantly improved, the hydrophobic properties are enhanced, and the aging resistance of the coating is also improved due to the inorganic components only.
Smart Images

Figure CN119912854A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to an enhanced wear-resistant transparent nano coating and a preparation method and application thereof. Background Art
[0002] Photovoltaic modules are used outdoors for many years and are exposed to the environment such as wind, sun, rain, etc. The performance of the module materials has been significantly degraded, resulting in a decrease in the photoelectric conversion efficiency. With the increase in solar energy installed capacity, how to improve the power generation efficiency of photovoltaic modules is an urgent issue. The factors that affect the power generation efficiency of photovoltaic modules mainly include the material composition of photovoltaic modules and environmental factors, and the impact of dust accumulation is the most significant among environmental factors. Photovoltaic glass, as the cover glass of conventional photovoltaic modules, is easy to absorb dust caused by atmospheric and traffic exhaust pollutants during daily use, resulting in dust accumulation on the surface of photovoltaic glass, which hinders the entry of sunlight and thus leads to a decrease in photovoltaic efficiency; secondly, since the thermal resistance of dust is greater than that of air, the accumulation of dust will also cause the internal temperature of photovoltaic modules to rise, accelerate the aging of photovoltaic modules, and reduce their service life; finally, dust is deposited on the surface of photovoltaic glass, and will also undergo a slow chemical reaction, making the glass surface rough, causing a greater degree of diffuse reflection, and reducing the visible light transmittance. Studies have shown that 8 days of natural dust accumulation will reduce the relative transmittance of the photovoltaic module surface glass by about 20%, and the battery conversion efficiency will also decrease exponentially with the increase of surface dust density. Therefore, in order to ensure the battery conversion efficiency, the photovoltaic glass must be cleaned regularly. Cleaning photovoltaic glass is a very costly task. Therefore, how to reduce the frequency of photovoltaic glass cleaning has become an urgent task that needs to be solved.
[0003] Chinese patent CN115491123A describes a self-cleaning hydrophobic dust-free nano-protective coating for photovoltaic glass and its preparation method, which includes the following steps: putting organic polysilazane resin and inorganic polysilazane resin into a beaker and adding a mixed solvent, stirring at a speed of 500 revolutions per minute on a high-speed mixer for 10 minutes to mix evenly, and then adding silane coupling agent, PMA-ST, nano-tin dioxide dispersion TEGO5000N, adjusting the speed to 1500 revolutions per minute and continuing to stir for 30 to 60 minutes to obtain a self-cleaning antistatic dust-free nano-coating. This method uses organic resin as an adhesive, which has poor aging resistance. It is easy to turn yellow after being applied to the glass surface for a long time, affecting the transmittance, and the film layer is only tested with a pencil, and its wear resistance is insufficient. Chinese patent CN116478602 A discloses a water-soluble, highly wear-resistant and anti-rust coating based on nanoparticles and a preparation method thereof, wherein the preparation comprises the following steps: weighing each component; then weighing a polymer with a hydroxyl functional group and a polymer with an amino functional group and adding them to an alcohol ether solvent, stirring continuously for 0.2 to 0.4 hours, adding a nano zirconium oxide dispersion, a nano graphene dispersion, a nano molybdenum disulfide dispersion, a composite zinc phosphate, and a thickener, stirring and dispersing continuously for 30 to 60 minutes, and obtaining a dispersion A; then adding an adhesion promoter and an anti-flash rust additive to the dispersion A, dispersing for 10 minutes at 1500 rpm, adding an organic carbon black slurry, adjusting the speed of the dispersing machine to 1000 rpm and dispersing for 10 minutes to obtain a dispersion B; finally, adding water to the dispersion B and stirring evenly, and filtering through a 250-mesh filter. The composition contains organic matter, has poor aging resistance, and the coating obtained by the coating also has poor wear resistance. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide an enhanced wear-resistant transparent nano coating and a preparation method and application thereof.
[0005] In order to achieve the above purpose, the technical solution of the present invention is: an enhanced wear-resistant transparent nano coating, which comprises 0-0.3wt% of hectorite, 53.6wt%-61.2wt% of acidic silica sol, 10.7wt%-12.2wt% of epoxy resin, 6.1wt%-17.8wt% of alkaline catalyst, and 17.8wt%-20.4wt% of alcohol solvent.
[0006] In a preferred embodiment of the present invention, the specific preparation steps of the acidic silica sol are as follows: an alcohol solvent, tetraethyl orthosilicate (TEOS) and a silane coupling agent are mixed at a mass ratio of 30-50:10-20:5-10 for 3-7 minutes, an acidic catalyst is added dropwise, and then stirred at room temperature of 50°C for 1.5-2.5 hours, ultrasonicated for 1.5-2.5 hours, and allowed to stand for 4-5 weeks to obtain an acidic silica sol.
[0007] Further preferably, the acidic catalyst is an inorganic acid or an organic acid, wherein the inorganic acid is preferably a mixture of one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, etc., and the organic acid is preferably a mixture of one or more of formic acid, acetic acid, propionic acid, etc., and the concentration of the acidic catalyst is 0.01 to 0.50 mol / L.
[0008] Further preferably, the silane coupling agent includes a mixture of one or more silane coupling agents having functional groups such as amino, hydroxyl, carboxyl, sulfonic acid, vinyl, epoxy, methacryloxy, mercapto or urea.
[0009] In a preferred embodiment of the present invention, the epoxy resin is a water-soluble or water-insoluble epoxy resin, preferably a water-soluble epoxy resin.
[0010] In a preferred embodiment of the present invention, the alcohol solvent includes a mixture of one or more of C1-C6 alcohols (methanol, ethanol, propanol, butanol, pentanol, hexanol).
[0011] In a preferred embodiment of the present invention, the alkaline catalyst comprises an inorganic hydroxide, preferably LiOH, NaOH, KOH, and the like.
[0012] A method for preparing a reinforced wear-resistant transparent nano coating comprises the following steps: mixing acidic silica sol and epoxy resin in proportion, then dropwise adding a mixed solution of an alkaline catalyst and an alcohol solvent mixed in proportion, and stirring for 10 to 20 minutes; then adding a reinforcing agent hectorite in proportion, mixing and stirring for 0.5 to 1.5 hours, and ultrasonicating for 0.5 to 1.5 hours.
[0013] The invention discloses an enhanced wear-resistant transparent hydrophobic coating prepared by coating with an enhanced wear-resistant transparent nano coating.
[0014] A method for preparing an enhanced wear-resistant transparent hydrophobic coating comprises the following steps:
[0015] (1) polishing the glass substrate with a cerium oxide solution to remove surface impurities and the like to ensure a good coating effect, then ultrasonicating for 15 to 25 minutes, drying, irradiating with an ozone machine for surface hydroxylation, and taking out for use;
[0016] (2) placing the glass substrate treated in step (1) on a spin coater and spin coating the surface of the glass substrate with an enhanced wear-resistant transparent nano coating;
[0017] (3) pre-curing and curing the sample after surface spin coating in step (2), and then removing the organic components by high temperature treatment, the high temperature treatment temperature is 350-450° C., and the holding time is 20-40 min;
[0018] (4) placing the sample treated in step (3) in a hydrothermal reactor, adding 0.001-0.01 wt% fluorosilane for surface modification, performing a hydrothermal reaction at 100-200°C for 40-80 min, and then performing evaporation at a temperature of 100-200°C for 40-80 min to obtain an enhanced wear-resistant transparent hydrophobic coating.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention is based on the gelation of acidic silica sol and the phase separation process of epoxy resin, and then utilizes the physical properties and special structure of lithium soapstone to prepare an enhanced wear-resistant transparent nano coating. The coating obtained after coating with the coating has a "honeycomb" surface morphology, and the Vickers hardness and hydrophobicity of the coating are improved;
[0021] (2) The coating prepared by the enhanced wear-resistant transparent nano coating prepared by the present invention has excellent enhanced wear resistance and transparency properties. At the same time, the prepared coating contains only inorganic components and has good aging resistance, and has potential application prospects in multiple fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a surface morphology of the coating after the enhanced wear-resistant transparent nano coating prepared in Example 3 of the present invention is applied;
[0023] Figure 2 This is a physical picture of the coating prepared after applying the enhanced wear-resistant transparent nano coating prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is described in more detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0025] The acidic silica sol used in the following examples and comparative examples was prepared by the following method: anhydrous ethanol (41.9 g), TEOS (17.3 g) and silane coupling agent KH560 (8.5 g) were added to a clean beaker in sequence and stirred for 5 minutes to obtain a mixed solution A; deionized water (15.8 g) and 1 vol% HNO3 (4.2 g) were added to another clean beaker to obtain a mixed solution B; the mixed solution B was added dropwise to the mixed solution A, and the obtained mixed solution was stirred at room temperature for 2 h, ultrasonicated for 2 h, and allowed to stand for 5 weeks to obtain an acidic silica sol.
[0026] Example 1
[0027] A reinforced wear-resistant transparent nano coating, the components of which are as follows: 3.0g of acidic silica sol, 0.6g of epoxy resin, 1.0g of KOH, 1.0g of anhydrous ethanol, and 0.0028g of laponite. The preparation method thereof comprises the following steps: mixing the acidic silica sol and the epoxy resin in proportion, then adding a mixed solution of KOH and anhydrous ethanol dropwise, and stirring for 15 minutes; then adding laponite, mixing and stirring for 1 hour, and ultrasonicating for 1 hour to obtain the reinforced wear-resistant transparent nano coating.
[0028] The enhanced wear-resistant transparent nano coating is spin-coated on a glass substrate to obtain an enhanced wear-resistant transparent hydrophobic coating, comprising the following steps:
[0029] (1) Ordinary white glass sold on the market is used for grinding and polishing with a sander, and a cerium oxide solution is used as a polishing liquid. The polished glass is then ultrasonicated in deionized water, and then dried in a constant temperature drying oven. Finally, the dried glass is irradiated in an ultraviolet ozone cleaning machine for 10 minutes to remove organic molecules and perform surface hydroxylation to form highly reactive hydroxyl groups;
[0030] (2) dripping the prepared enhanced wear-resistant transparent nano coating onto the pretreated glass surface, spinning it on a spin coater at a speed of 600 rpm for 10 seconds, and then placing the coated glass in a blast drying oven for pre-curing for 30 minutes, then curing for 120 minutes, and then heating it to 400°C in a high-temperature furnace and keeping it warm for 30 minutes to remove organic components in the film layer;
[0031] (3) The sample prepared in step (2) is placed in the inner tank of a hydrothermal reactor, and then 40 μL of heptadecafluorodecyltrichlorosilane (FAS) is added dropwise, and the reactor is placed in a 150° C. oven for 1 hour. After cooling, the sample is taken out, and then the sample is placed in a 180° C. oven for 1 hour, to finally obtain an enhanced wear-resistant transparent hydrophobic coating.
[0032] Example 2
[0033] A reinforced wear-resistant transparent nano coating, the components of which are as follows: 3.0g of acidic silica sol, 0.6g of epoxy resin, 1.0g of KOH, 1.0g of propanol, and 0.0056g of laponite.
[0034] A method for preparing an enhanced wear-resistant transparent nano coating is the same as that in Example 1. The enhanced wear-resistant transparent nano coating is spin-coated on a glass substrate to prepare an enhanced wear-resistant transparent hydrophobic coating, and the specific preparation steps are the same as those in Example 1.
[0035] Example 3
[0036] A reinforced wear-resistant transparent nano coating, the components of which are as follows: 3.0g of acidic silica sol, 0.6g of epoxy resin, 1.0g of KOH, 1.0g of anhydrous ethanol, and 0.0084g of laponite.
[0037] A method for preparing an enhanced wear-resistant transparent nano coating is the same as in Example 1. The enhanced wear-resistant transparent nano coating is spin-coated on a glass substrate to prepare an enhanced wear-resistant transparent hydrophobic coating. The specific preparation steps are the same as in Example 1. The surface morphology of the coating is as follows: Figure 1 shown.
[0038] The wear resistance test of the enhanced wear-resistant transparent hydrophobic coating prepared in this embodiment was carried out: the X-5750-J reciprocating linear abrader produced by Shenzhen Xinhengsen Trading Co., Ltd. was used to test the wear resistance of the sample. Flannel cloth was used as the friction medium, and the sample was polished at a rate of 40 cycles / minute under a pressure of 30 kPa. After 2000 cycles of linear polishing, the surface structure of the enhanced wear-resistant transparent hydrophobic coating prepared in this embodiment remained intact, and the film layer cross-sectional thickness retention rate was 92%, indicating that the coating has excellent wear resistance. The actual picture of the enhanced wear-resistant transparent hydrophobic coating of this embodiment is shown in the figure below. Figure 2 As shown in the figure, it can be seen that the optical properties of the glass are good, and the coating is evenly covered on the glass surface, which is smooth and flat without bubbles or peeling.
[0039] Example 4
[0040] A reinforced wear-resistant transparent nano coating, the components of which are as follows: 3.0g of acidic silica sol, 0.6g of epoxy resin, 1.0g of KOH, 1.0g of anhydrous ethanol, and 0.0112g of hectorite.
[0041] A method for preparing an enhanced wear-resistant transparent nano coating is the same as that in Example 1. The enhanced wear-resistant transparent nano coating is spin-coated on a glass substrate to prepare an enhanced wear-resistant transparent hydrophobic coating, and the specific preparation steps are the same as those in Example 1.
[0042] Example 5
[0043] A reinforced wear-resistant transparent nano coating, the components of which are as follows: 3.0g of acidic silica sol, 0.6g of epoxy resin, 1.0g of KOH, 1.0g of anhydrous ethanol, and 0.014g of laponite.
[0044] A method for preparing an enhanced wear-resistant transparent nano coating is the same as that in Example 1. The enhanced wear-resistant transparent nano coating is spin-coated on a glass substrate to prepare an enhanced wear-resistant transparent hydrophobic coating, and the specific preparation steps are the same as those in Example 1.
[0045] Comparative Example 1
[0046] A wear-resistant transparent nano coating comprises the following components: 3.0 g of acidic silica sol, 0.6 g of epoxy resin, 1.0 g of KOH and 1.0 g of anhydrous ethanol.
[0047] A method for preparing a wear-resistant transparent nano coating is the same as that in Example 1. The wear-resistant transparent nano coating is spin-coated on a glass substrate to prepare a wear-resistant transparent hydrophobic coating, and the specific preparation steps are the same as those in Example 1.
[0048] The following tests were performed on the enhanced wear-resistant transparent hydrophobic coatings prepared in Examples 1-5 and the wear-resistant transparent hydrophobic coating prepared in Comparative Example 1:
[0049] Surface morphology: The surface morphology of the samples was characterized using a SU-70 scanning electron microscope produced by Hitachi at an accelerating voltage of 5 kV.
[0050] Hardness test: The hardness of the sample was tested using a 1-1000gf digital display micro Vickers hardness tester produced by Beijing Times Peak Technology Co., Ltd. The applied force was 0.098N and the action time was 15s.
[0051] Static contact angle test: The test was conducted using a JCY-4 contact angle measuring instrument produced by Shanghai Fangrui Company. The test liquid was deionized water and the test volume was 5 μL.
[0052] Transmittance test: A Lambda 750S UV-Vis-NIR spectrophotometer produced by Perkin Elmer was used.
[0053] The performance test results of the wear-resistant transparent hydrophobic coatings prepared in Examples 1-5 and Comparative Example 1 are shown in Table 1.
[0054] Table 1 Performance test results of wear-resistant transparent hydrophobic coatings prepared in Examples 1-5 and Comparative Example 1
[0055] performance Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Hardness(Hv) 449.5 483.8 500.5 511.0 483.6 377.9 Contact angle (°) 132 135 136 134 134 127 Transmittance (%) 89.9 89.5 89.2 89.0 88.8 89.0
[0056] It can be seen from the performance test results in Table 1 that, compared with Comparative Example 1, the addition of the enhancer to the coatings in Examples 1-5 has no effect on the visible light transmittance, and the hardness and hydrophobicity of the film layer are both improved.
[0057] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An enhanced wear-resistant transparent nano coating, characterized in that: The composition includes 0-0.3wt% of laponite, 53.6wt%-61.2wt% of acidic silica sol, 10.7wt%-12.2wt% of epoxy resin, 6.1wt%-17.8wt% of alkaline catalyst and 17.8wt%-20.4wt% of alcohol solvent.
2. The enhanced wear-resistant transparent nano coating according to claim 1, characterized in that: The preparation steps of the acidic silica sol are as follows: an alcohol solvent, tetraethyl orthosilicate and a silane coupling agent are mixed at a mass ratio of 30-50:10-20:5-10 for 3-7 minutes, an acidic catalyst is added dropwise, and then stirred at room temperature of 50° C. for 1.5-2.5 hours, ultrasonicated for 1.5-2.5 hours, and allowed to stand for 4-5 weeks to obtain the acidic silica sol.
3. The enhanced wear-resistant transparent nano coating according to claim 2, characterized in that: The acid catalyst is an inorganic acid or an organic acid, and the concentration of the acid catalyst is 0.01 to 0.50 mol / L.
4. The enhanced wear-resistant transparent nano coating according to claim 2, characterized in that: The silane coupling agent includes a mixture of one or more silane coupling agents having amino, hydroxyl, carboxyl, sulfonic acid, vinyl, epoxy, methacryloxy, mercapto or urea functional groups.
5. The enhanced wear-resistant transparent nano coating according to claim 1, characterized in that: The epoxy resin is a water-soluble or water-insoluble epoxy resin.
6. The enhanced wear-resistant transparent nano coating according to claim 1 or 2, characterized in that: The alcohol solvent includes a mixture of one or more of methanol, ethanol, propanol, butanol, pentanol and hexanol.
7. The enhanced wear-resistant transparent nano coating according to claim 1, characterized in that: The basic catalyst includes an inorganic hydroxide.
8. A method for preparing the enhanced wear-resistant transparent nano coating according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing acidic silica sol and epoxy resin in proportion, then dropwise adding a mixed solution of an alkaline catalyst and an alcohol solvent in proportion, and stirring for 10 to 20 minutes; then adding a reinforcing agent, hectorite, in proportion, mixing and stirring for 0.5 to 1.5 hours, and ultrasonicating for 0.5 to 1.5 hours.
9. An enhanced wear-resistant transparent hydrophobic coating made from the enhanced wear-resistant transparent nano coating as claimed in any one of claims 1 to 7.
10. A method for preparing the enhanced wear-resistant transparent hydrophobic coating according to claim 9, characterized in that: The steps include: (1) polishing the glass substrate with a cerium oxide solution to remove surface impurities, then ultrasonicating for 15 to 25 minutes, drying, irradiating with an ozone machine to perform surface hydroxylation treatment, and taking it out for use; (2) placing the glass substrate treated in step (1) on a spin coater and spin coating the surface of the glass substrate with an enhanced wear-resistant transparent nano coating; (3) pre-curing and curing the sample after surface spin coating in step (2), and then removing the organic components by high temperature treatment, the high temperature treatment temperature is 350-450° C., and the insulation time is 20-40 min; (4) placing the sample treated in step (3) in a hydrothermal reactor, adding 0.001-0.01 wt% fluorosilane, carrying out a hydrothermal reaction at 100-200°C for 40-80 min, and then performing evaporation at a temperature of 100-200°C for 40-80 min to obtain an enhanced wear-resistant transparent hydrophobic coating.
Citation Information
Patent Citations
Self-cleaning hydrophobic dust-free nano protective coating for photovoltaic glass and preparation method of self-cleaning hydrophobic dust-free nano protective coating
CN115491123A
Water-soluble high-wear-resistance antirust coating based on nanoparticles and preparation method thereof
CN116478602A